Increasing proportions of relapsing parasite species among imported malaria in China's Guangxi Province from Western and Central Africa. Issue 43 (September 2021) - Liu, Penglu; Shen, Lijie; Wang, Siqi; Qin, Pien; Si, Yu; Pan, Maohua; Zeng, Weilin; Qin, Yucheng; Chen, Xi; Zhang, Yanmei; Li, Cuiying; Xiang, Zheng; et al.
Abstract: Background: Travel-related malaria in non-endemic areas returning from endemic areas presents important challenges to diagnosis and treatment. Imported malaria to newly malaria-free countries poses further threats of malaria re-introduction and potential resurgence. For those traveling to places with high Plasmodium falciparum prevalence, prophylaxis against this parasite is recommended, whereas causal prophylaxis against relapsing malaria is often overlooked. Methods: We analyzed a cluster of imported malaria among febrile patients in Shanglin County, Guangxi Province, China, who had recent travel histories to Western and Central Africa. Malaria was diagnosed by microscopy and subsequently confirmed by species- and subspecies-specific PCR. Plasmodium vivax was genotyped using a barcode consisting of 42 single nucleotide polymorphisms. Results: Investigations of 344 PCR-confirmed malaria cases revealed that in addition to Plasmodium falciparum being the major parasite species, the relapsing parasites Plasmodium ovale and P. vivax accounted for 40% of these imported cases. Of the 114 P. ovale infections, 65.8% and 34.2% were P. ovale curtisi and P. ovale wallikeri, respectively, with the two subspecies having a 2:1 ratio in both Western and Central Africa. Phylogenetic analysis of 14 P. vivax isolates using a genetic barcode demonstrated that 11 formed a distinct clade from P. vivax populations from Eastern Africa. Conclusion: This study provides support for active P. vivax transmission in areas with the predominant Duffy-negative blood group. With relapsing malaria making a substantial proportion of the imported malaria, causal prophylaxis should be advocated to travelers with a travel destination to Western and Central Africa. Highlights: We investigated a cluster of imported malaria cases in a southern Chinese county. Patients had travel histories to malaria-endemic areas of West and Central Africa. Relapsing malaria P. ovale and P. vivax accounted for 40% of PCR-confirmed cases. The two P. ovale subspecies had a 2:1 ratio in both West and Central Africa. Some P. vivax strains formed a separate group different from East African parasites.